Az ipar szerepe a „szocialista” gazdaság- és területfejlesztési politikában - Barta, Györgyi (Tér és Társadalom, 1991)
The situation was easily assessable, and the tasks were clear for the regional experts of the socialist era: industry (autarchy and over-emphasized defence objectives gave priority to heavy industry) was the engine of economic development policy, which was also based on industrial development. It must be added, that little attention was paid on details. In stead of developing a structurally well-balanced and efficient regional policy which meets the characteristics of different regions and then can be fitted into an organic regional economy, the primary objective was to increase the number of industrial workplaces. Extensive approach, which put the sign of equality between development and physical extension, got into trouble already in the 1970s. How can the decreasing number of industrial employees, and the decreasing pace of the development of industrial production be interpreted? These were the signs of the crisis of socialism, and the exhaust of resources, the decrease of free labour and the lack of capital became characteristic. Besides all these phenomena, industry had preserved its special role in regional development policy all the time, though the importance of industry was handled and interpreted in a more tinged way in the whole society. The present situation of industry is characterized by overall decline: industrial capacities are becoming limited, the number of people dismissed from industry is unstoppably increasing, the extensive markets of our industrial products are lost, and new markets are difficult to find, industrial production is decreasing both in absolute terms and also as compared to the national income. What is the present case then now? What we are faced is the temporary crisis of industry, which follows from the transitional character of our socio-economic development? Or probably, Hungary has also got into the phase of post-industrial development, where industry loses its previous role? Answering these questions is indispensible to elaborate the new regional-development policy, because regional development always has to use the most modern and dynamic elements of socio-economic development.